Five ways to get a grip on evaluating and improving educational continuity in health professions education programs - Lee, Ann Shuk On; Ross, Shelley (Canadian Medical Education Journal, 2020)
Presence of educational continuity is essential for progressive development of competence. Educational continuity appears to be a simple concept, but in practice, it is challenging to implement and evaluate because of its multifaceted nature. In this Black Ice article, we present some practical tips to help avoid misunderstandings and irregularities in implementation for those involved in evaluating and improving educational continuity in health professions education programs.